“Roberto Rodríguez” General Teaching Hospital of Moron, Ciego De Avila, Cuba, Neurosurgery and Pediatric Intensive Care Services Pediatric Neuromonitoring in Severe Head Trauma - Daysi Abreu Pérez; Angel J. Lacerda Gallardo; Jose Antonio Gálvez (Neurotrauma Reports)
Among all types of trauma in children, traumatic brain injury has the greatest potential for the development of devastating consequences, with nearly three million affected each year in the world. A controlled, nonrandomized experimental study was carried out in pediatric patients with severe traumatic brain injury, whose objective was to evaluate the use of continuous multimodal neuromonitoring (MMN) of intracranial parameters as a guide in the treatment of children of different age-groups. The patients were divided into two groups according to the treatment received; clinical and imaging monitoring was performed in both. Group I included those whose treatment was guided by MMN of intracranial parameters such as intracranial pressure, cerebral perfusion pressure, and intracranial compliance, and group II included those who had only clinical and imaging monitoring. Eighty patients were studied, 41 in group I and 39 in group II. There were no significant differences between the groups with respect to the sociodemographic variables and the results; as a consequence, both forms of treatment were outlined, for patients with MMN and for those who only have clinical and imaging monitoring. It is concluded that both treatment schemes can be used depending on technological availability, although the scheme with MMN is optimal.